PENGARUH INTELLECTUAL CAPITAL, STRUKTUR MODAL DAN KOMITE AUDIT TERHADAP KINERJA KEUANGAN - Darwanti, Apri; Purwasih, Desy (JURNAL AKUNTANSI BARELANG, 2024)
This research aims to provide empirical evidence on the influence of Intellectual Capital independence,Capital Structure, and Audit Committee on Financial Performance in industrial sector companies listed on the Indonesia Stock Exchange for the period 2018-2022. The research sample consists of 17 industrial sector companies determined based on purposive sampling method. The methods used include multiple linear regression,descriptive statistical test,panel data regression model analysis,model selection test with the chosen Random Effect Model,classical assumption test,multiple linear test, and hypothesis testing with the aid of statistical data processing using e-views version 12. The result of this study indicate that Intellectual Capital,Capital Structure, and Audit Committee simultaneously have a significant effect on Financial Performance,and the t-test shows that Intellectual Capital has a significant effect on Financial Performance. However, the variables of Capital Structure and Audit Committee do not have a significant effect on Financial Performance.